Konsep Kepatuhan Syariah dalam Pembiayaan Musyarakah pada Bank Syariah berdasarkan Maqashid Syariah: The Concept of Sharia Compliance in Musyarakah Financing in Islamic Banks Based on Maqasid Sharia - Pulungan, Putri Hasanah; Hasibuan, Afifah Khairani; Hasibuan, Abdul Nasser (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2025)
Musyarakah financing is one of the main contracts in Islamic banking, based on the principle of capital partnership between banks and customers, with profits and losses shared according to an agreed ratio (nisbah). This product represents the most widely used financing instrument in Indonesian Islamic banking, as reflected in the Indonesian Sharia Financial Development Report published by the Financial Services Authority (OJK), which stated that musyarakah financing accounted for 49.86% of total financing distribution as of December 2024. This study aims to provide a theoretical foundation for sharia compliance in musyarakah financing within Islamic banks, and to enhance understanding of how Islamic banks ensure compliance when channeling financing through this contract. The research employs a descriptive qualitative approach in the form of library research, using theoretical and conceptual analysis. The findings indicate that sharia compliance in musyarakah financing is examined through four approaches: contract (‘aqd), maqashid al-shariah, documentation, and accounting/financial reporting. The contract approach emphasizes that musyarakah transactions must fulfill their essential pillars and conditions, including clarity of capital contribution, profit-sharing ratio, and proportional loss bearing. From the maqashid al-shariah perspective, musyarakah not only safeguards wealth but also ensures the circulation of assets so they are not concentrated in the hands of a few, promotes contractual clarity, and supports economic stability by encouraging productive activities in the real sector. In terms of documentation, the form and substance of musyarakah agreements must comply with Islamic legal principles and be supervised by the Sharia Supervisory Board in their preparation. Meanwhile, accounting and financial reporting must reflect the amount of capital contributed by each party, the mechanism of profit distribution based on the agreed ratio, and the allocation of losses proportionally to the capital. Musyarakah financial statements are required to disclose capital positions, business outcomes, and profit distribution in a transparent manner to avoid practices resembling riba.